Topical Issues of Drug Safety, Possibilities of Improving of Pharmacovigilance - M. V. Zhuravleva; B. K. Romanov; G. I. Gorodetskaya; O. V. Muslimova; V. S. Krysanova; E. Yu. Demchenkova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2019)
Since 2010, Russia has been developing new drug legislation, internal quality control and safety of medical organizations, and has developed algorithms for submitting Individual Case Safety Reports (ICSR) using an automated information system. On April 1, 2019, Russia launched an updated national database of ICSR, which uses the international ICH E2B data standard, which may increase the amount of reporting to the Uppsala monitoring center. This publication covers the key aspects of pharmacovigilance system development in the Russian Federation. The analysis of pharmacovigilance structure in the Russian Federation is carried  out, its main problems are designated. Presents methods to identify causal relationships between adverse reaction and drug, evaluation of its degree of validity (questionnaires, algorithms, and scale), as already recommended by the WHO, and the new modifi ed versions. The expediency of using a scale for determining the degree of reliability of a causal relationship «an undesirable reaction - drug interaction» when analyzing spontaneous reports of undesirable reactions that may be caused by drug interactions is noted. An effective method of detection and prevention of adverse reactions is presented - the Global Trigger Tool (GTT). The question of the need for motivation and training of medical personnel in the correct design of spontaneous messages, as well as methods of identifying the causal relationship between adverse reactions of drugs. The directions of optimization of pharmacovigilance system are proposed, including methods of more effective active surveillance in the identifi cation and prevention of adverse reactions.